Altered Plasma microRNA Signature in Hospitalized COVID-19 Patients Requiring Oxygen Support - Sandra Franco; Lourdes Mateu; Raquel Pluvinet; Jose Francisco Sanchez-Herrero; Ruth Toledo; Lauro Sumoy; Marta Massanella; Miguel Angel Martinez (Microorganisms, 2024)
To discover potential micro(mi)RNA biomarkers of SARS-CoV-2 infection and disease progression, large-scale deep-sequencing analysis of small RNA expression was performed on plasma samples from 40 patients hospitalized for SARS-CoV-2 infection (median 13.50 [IQR 9–24] days since symptoms initiation) and 21 healthy noninfected individuals. A total of 1218 different miRNAs were identified. When compared with healthy noninfected donors, SARS-CoV-2-infected patients showed significantly (fold change [FC] > 1.2 and adjusted p [padj] < 0.05) altered expression of 190 miRNAs. The top-10 differentially expressed (DE) miRNAs were miR-122-5p, let-7b-5p, miR-146a-5p, miR-342-3p, miR-146b-5p, miR-629-5p, miR-24-3p, miR-12136, let-7a-5p, and miR-191-5p, which displayed FC and padj values ranging from 153 to 5 and 2.51 × 10−32 to 2.21 × 10−21, respectively, which unequivocally diagnosed SARS-CoV-2 infection. No differences in blood cell counts and biochemical plasma parameters, including interleukin 6, ferritin, and D-dimer, were observed between COVID-19 patients on high-flow oxygen therapy, low-flow oxygen therapy, or not requiring oxygen therapy. Notably, 31 significantly deregulated miRNAs were found, when patients on high- and low-flow oxygen therapy were compared. SARS-CoV-2 infection generates a specific miRNA signature in hospitalized patients. Specific miRNA profiles are associated with COVID-19 prognosis in patients requiring oxygen flow.